THE STUDY OF THE QUALITATIVE COMPOSITION OF THE MICROFLORA OF BIODRINKS BASED ON CAMEL'S MILK - K. S. Kulazhanov; F. T. Dikhanbayeva; E. CH. Tasturganova (Алматы технологиялық университетінің хабаршысы, 2021)
The main raw material in the production of all dairy products is raw milk. The quality of dairy products is determined by a set of indicators, the most important of which are safety indicators. In this research work the study of the qualitative composition of the microflora of biodrinks based on camel's milk. According to the research results, the content of lactic acid microorganisms in biodrinks in the amount of 3700*103-5000*103 CFU / g (cm3), which proves the useful properties of the studied dairy products.